2009
DOI: 10.1007/bf03327626
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heavy metals in the core sediments of a tropical wetland system

Abstract: Five sediment cores from the fresh water region of the Vembanad wetland system were studied for the trace element contents The average concentration of iron, manganese, nickel, copper, zinc, cadmium, lead, mercury and chromium were determined. The core samples were collected using gravity type corer, digested with a mixture of nitric acid and perchloric acid and analyzed by atomic absorption spectrophotometry. Heavy metals such as iron, copper, nickel and zinc reported enrichment towards the surface of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(127 citation statements)
references
References 21 publications
3
113
0
4
Order By: Relevance
“…Rusan et al (2007) rightly noted that there is inconsistency in research findings on the impact of wastewater irrigation on soil micronutrients and heavy metals. However, results in this study tally with the findings of some previous studies, including: 1) the build-up of heavy metals such as Cd, Hg, Ni and Pb and micronutrients such as Cu, Fe, Mn and Zn in the upper layers of the soil or sediment cores (Mancino and Pepper, 1992;Rusan et al, 2007;Harikumar et al, 2009); 2) increases in soil Al, Fe and Mn with wastewater irrigation (Mohammad and Mazahreh, 2003); 3) variable and inconsistent responses of soil micronutrients under different crop types; and 4) the significance of soil textural differences in influencing the accumulation of heavy metals and micronutrients in soils under wastewater irrigation (Ivan and Earl, 1972;Donahue et al, 1977).…”
Section: Micronutrientssupporting
confidence: 89%
“…Rusan et al (2007) rightly noted that there is inconsistency in research findings on the impact of wastewater irrigation on soil micronutrients and heavy metals. However, results in this study tally with the findings of some previous studies, including: 1) the build-up of heavy metals such as Cd, Hg, Ni and Pb and micronutrients such as Cu, Fe, Mn and Zn in the upper layers of the soil or sediment cores (Mancino and Pepper, 1992;Rusan et al, 2007;Harikumar et al, 2009); 2) increases in soil Al, Fe and Mn with wastewater irrigation (Mohammad and Mazahreh, 2003); 3) variable and inconsistent responses of soil micronutrients under different crop types; and 4) the significance of soil textural differences in influencing the accumulation of heavy metals and micronutrients in soils under wastewater irrigation (Ivan and Earl, 1972;Donahue et al, 1977).…”
Section: Micronutrientssupporting
confidence: 89%
“…Metals concentrations of Zn, Cr, Cr and Pb from Lake Hawassa sediment as compared to the probable-effects-level (PEL) guidelines for toxic biological effects established and sediment-quality guidelines by USEPA [31], the present results revealed that metals concentration of sediment showed higher than the level of those elements set by the guidelines. Moreover, metals concentrations in the sediment including mercury exceeded the maximum acceptable levels cited by Frances [13].…”
Section: Metals Concentrations In Sedimentmentioning
confidence: 56%
“…A PLI value greater than 1 is polluted, whereas a PLI value less than 1 indicates no pollution [22].…”
Section: Geo-accumulation Index (I-geo)mentioning
confidence: 99%